Helpful little mechanic: ladybird - Eustace, Margaret; Kenyon, Tony (Ladybird London, 2005)
The Little Mechanic is sure he knows what's wrong with Mr Grenville Granville's great big shiny red car. But the other mechanics won't let him help. "Just go anmd make us all a drink", they keep saying.